EKSPLORASI CETAK FOTOGRAFI VANDYKE PADA MATERIAL KULIT - Junaidi Salam (Narada : Jurnal Desain dan Seni, 2019)
As part of the fashion material repertoire, leather has a lot of travel in the exploration and development of material functions, both technological development and the development of aesthetic basic material fashion products, so designers often use this material to increase the high economic value in the fashion industry. old print photography has indeed been abandoned a lot over the times and advances in photographic technology, but in retrospect, it has revived the passion for the search for unique aesthetic values of the old photographic processes and characteristics. This study focuses on experiments with Vandyke's photographic printing on leather material, especially in producing character and the application of photographic aesthetics into fashion material. This research is driven by a number of basic assumptions about the possibility of Vandyke printing applied to leather material, as well as efforts to produce realistic visual motifs in the style of retrospective photography techniques. While the effort that can be done is to determine the variable composition of chemicals in the Vandyke process towards the characteristics of the leather material that has been determined in a laboratory experiment.